Cryptomonas indica sp. nov. (Cryptophyceae: Cryptomonadales), a new species described from the Western Ghats, India - Gusev, Evgeniy; Karthick, Balasubramanian; Martynenko, Nikita; Shkurina, Nataliya; Kulikovskiy, Maxim (Phytotaxa, 2021)
A new species, Cryptomonas indica sp. nov., is described from Western Ghats, India, based on morphological and molecular data. Phylogenetic relationships inferred from nuclear small and large subunit ribosomal DNA, internal transcribed spacer 2, and plastid psbA sequences show that the new species forms a separate lineage on the phylogenetic tree of the genus Cryptomonas. This new species is included in the basal clade of Cryptomonas tree, which consists of undescribed taxa from Europe and South Korea. Cells of this species are up to 19 µm in length, elliptical to slightly asymmetrical in broad view, and have a plastid with four pyrenoids. Cryptomonas indica has been observed in one locality, the Northern region of the Western Ghats. Notably, this is the first Cryptomonas taxon described from the Indian subcontinent with both morphology and molecular information.